In vitro digestion of salmon: Influence of processing and intestinal conditions on macronutrients digestibility. (16th April 2021) - Asensio-Grau, Andrea; Calvo-Lerma, Joaquim; Heredia, Ana; Andrés, Ana
Highlights: Raw, marinated salmon were subjected to in vitro digestion process. Lipid and protein digestibility were studied in different intestinal conditions. Food processing was the major determinant in protein digestion. Lipolysis was largely affected by the intestinal conditions. Results of this study could orient dietary recommendations for salmon intake. Abstract: Salmon is the main dietary source of omega-3 lipids and contains high-biological value protein. However, processing techniques could affect macronutrient digestibility. Also, altered intestinal conditions, particularly given in pancreatic insufficiency, could threaten digestibility. This study tested both hypotheses by subjecting raw, marinated and microwave-cooked salmon to static in vitro digestion under healthy (pH 7, bile concentration 10 mM) and altered (pH 6, bile 1 or 10 mM) intestinal conditions with different pancreatin concentrations. In the standard conditions, proteolysis was not affected by processing, but lipolysis decreased in marinated (46%) and raw salmon (57%) compared to the cooked matrix (67%). In altered conditions, proteolysis and lipolysis decreased to different extents depending on the treatment. Overall, processing affected proteolysis the most (f-ratio = 5.86), while intestinal conditions were the major determinants of lipolysis (f-ratio = 58.01). This study could set the ground to establish dietary recommendations of salmon for specific population groups.